Breaking point of the harmony between Gd diffused Bi-2223 slabs with diffusion annealing temperature - Aydin, Hüseyin; Babanli, Arif; Altintas, S. P.; Asikuzun, E.; Soylu, N.; Dogruer, M.; Ozturk, O.; Terzioglu, C.; Yildirim, G. (Springer Science and Business Media LLC, 2013)
This comprehensive study reports the role of annealing temperature on the microstructural, superconducting and mechanical characteristics of the Gd diffused Bi-2223 superconducting ceramics produced by the conventional solid-state reaction route at 840 °C for the annealing duration of 48 h. For the material characterization, the standard experimental methods such as dc resistivity (ρ-T), transport critical current density, X-ray powder diffraction, scanning electron microscopy and Vickers microhardness measurements are performed systematically. All the results obtained show that all the measured characteristic properties, being in charge of the applications in the industry, engineering and technology, improve until a certain diffusion annealing temperature of 800 °C beyond which they tend to degrade considerably. The increase in the properties is mostly related to the transition from the inherent overdoped state of the pure Bi-2223 material to optimum doped state with the diffusion annealing temperature, confirming the penetration of the sufficient Gd nanoparticles into the crystal structure. On the other hand, the suppression in the superconducting properties stems from the appearance of the porosity, defects, disorder and localization problem in the polycrystalline Bi-2223 superconducting matrix. This is attributed to the decrement of the average crystallite size and mobile hole concentration in the Cu–O2 layers and especially the retrogression of the crystallinity in the system. As for the mechanical characteristics, Vickers microhardness measurements exerted in the applied indentation test load range of 0.245–2.940 N indicate that the Gd diffused bulk superconducting samples exhibit the typical indentation size effect behavior. With the enhancement in the annealing temperature up to 800 °C, the significant increase in the elastic modulus, yield strength and fracture toughness is one of the most striking points in the paper. The long and short of it is that the excess diffusion annealing temperature damages the fundamental characteristics of the Bi-2223 system.